The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1172/jci118716
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I is required for cholesteryl ester accumulation in steroidogenic cells and for normal adrenal steroid production.

Abstract: In addition to its ability to remove cholesterol from cells, HDL also delivers cholesterol to cells through a poorly defined process in which cholesteryl esters are selectively transferred from HDL particles into the cell without the uptake and degradation of the lipoprotein particle. The HDLcholesteryl ester selective uptake pathway is known to occur in human, rabbit, and rodent hepatocytes where it may contribute to the clearance of plasma cholesteryl ester. The selective uptake pathway has been studied most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
136
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 59 publications
(35 reference statements)
15
136
0
2
Order By: Relevance
“…30 Patients with obesity, insulin resistance, and diabetes have reduced endothelial function even without clinical evidence of cardiovascular disease. 31,32,33 Although endothelial function measurement has not been used as a routine clinical screening tool, clinical studies have demonstrated that endothelial dysfunction is an independent predictor of future cardiovascular events. 34,35 Therapeutic agents such as metformin and PPAR␥ agonists partially restore endothelial function in patients with diabetes.…”
Section: What Processes Cause Diabetic Toxicity?mentioning
confidence: 99%
“…30 Patients with obesity, insulin resistance, and diabetes have reduced endothelial function even without clinical evidence of cardiovascular disease. 31,32,33 Although endothelial function measurement has not been used as a routine clinical screening tool, clinical studies have demonstrated that endothelial dysfunction is an independent predictor of future cardiovascular events. 34,35 Therapeutic agents such as metformin and PPAR␥ agonists partially restore endothelial function in patients with diabetes.…”
Section: What Processes Cause Diabetic Toxicity?mentioning
confidence: 99%
“…4 -6). In addition to its role as a structural element of HDL, apoA-I stimulates cholesterol efflux, is the most potent activator of LCAT (7) and may be important for HDL interactions with scavenger receptor class B type 1 (8,9) and ABCA1 (10,11). * This work was supported in part by a group grant from the Canadian Institutes of Health Research.…”
Section: High Density Lipoproteins (Hdl)mentioning
confidence: 99%
“…In HDL, apoA-I is the principal physiological activator of lecithin-cholesterol acyltransferase (11)(12)(13). ApoA-I also promotes high affinity binding of HDL and rHDL particles to cells (14 -17), and analysis of apoA-I-deficient mice highlighted the importance of apoA-I for the delivery of HDL cholesterol to steroidogenic tissues via selective lipid uptake (18).…”
mentioning
confidence: 99%